Pengaruh Kualitas Pelayanan, Persepsi Harga dan Penyediaan Fasilitas Terhadap Kepuasaan Pelanggan Pada Klinik Duta Medika Pratama di Kota Bogor - Syafitri, Della; Pratomo, Anton Widio; Zuhdi, Saefudin (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Economic activity is currently experiencing rapid progress, overall growth is accompanied by the development of science and technology, making competition between markets more intense. Klinik Duta Medika Pratama is a health service provider located in the city of Bogor, providing a variety of medical services that can help the community in getting medical help. This study aims to (1) Know the effect of Service Quality on Customer Satisfaction (2) Know the effect of Price Perception on Customer Satisfaction (3) Know the effect of Facilities on Customer Satisfaction (4) Know the effect of Service Quality, Price Perception and Facilities together on Customer Satisfaction. (4) Knowing the effect of Service Quality, Price Perception and Facilities together on Customer Sat isfaction. This sample method is a non-probability sampling method with purposive sampling type with calculations using the Kretjie and Morgen formula. The number of respondents selected was 270 people who were patients of the Duta Medika Pratama Clinic. The research data was processed using SPSS 23 software. From the results of the analysis, it shows that partially (1) there is a positive and significant relationship between Service Quality and Customer Satisfaction. (2) there is a positive and significant relationship between Price Perception and Customer Satisfaction. (3) there is a positive and significant relationship between the Facility and Customer Satisfaction. (4) Service Quality, Price Perception and Facilities together have a positive and significant effect on Customer Satisfaction Keywords : Service Quality, Price Perception, Facilities and Customer Satisfaction